How Expensive is it to lose weight? - The financial cost of one such weight loss program - Richard M Fleming; Tapan K Chaudhuri (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Background: Obesity is the result of excess caloric consumption compared with caloric expenditure. Multiple approaches exist including pre-packaged meals. This study looked at just one proposed product and the cost of its use. Methods: Sixty premenopausal women were selected to participate in a weight reduction product composed of prepackaged soy protein. The soy protein product was designed as a meal replacement program. Changes in weight were measured and reported for one month. Results: The use of this soy product meal replacement program resulted in 7-pounds weight loss over four-weeks. Participants consumed an average of 3.75 servings of this soy chip product each day for an average of 105 packages of the soy chip product over the 4-week period of time. At an average price of $2.99 per package (plus tax and fees), this would cost each individual $313.95 to obtain an average weight loss of 7.3 pounds or $43.01 per pound. The calories consumed by the women in soy product ranged from 385 to 402.5 kCal per day. Conclusion: To lose 1-pound per week requires an energy deficit of 350 kCal per day or 3500 kCal per week. To lose 1.75 pounds per week - as seen in this study - would require a deficit of 612.5 kCal per day at a cost of $43.01 per pound of weight loss. This deficit is required on top of the caloric intake resulting from the soy product itself. Key points Questions: What is the financial cost for patients following prepackaged food replacement meals? Findings: The overall cost associated with food replacement meals is not negligible. In this instance, a heavily marketed meal replacement program cost $43.01 per pound of weight loss. Meaning: Given the significant numbers of weight loss programs currently marketed and the tendency for individuals to regain weight after cessation of such weight loss programs, this study raises concerns over the cost associated with such weight loss in the absence of more long term benefit including demonstration of improvement in cardiac health and reductions in cancer risk.